Framing Analysis of Kompas.com’s Coverage of Mobilization in the Social Movement Action of August 28–29, 2025 - Amanda Jingga Rambadani; Gladys Rotua Marito Manullang; Rinny Puspitasari; Aniqotul Ummah; Fullah Jumaynah (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to analyze how Kompas.com frames mobilization within the Social Movement Action of August 28–29, 2025. The study examines media construction through a framing analysis approach using four Kompas.com articles that implicitly address mobilization processes, action dynamics, and the actors involved. The data consist of online news texts selected based on their relevance to the issue of mass mobilization. The analysis identifies the structure of news discourse through the elements of diagnostic framing, prognostic framing, and motivational framing to understand how the media define problems, present solutions, and construct collective motivation in the context of social movements. The results show that mobilization by labor groups and university students is framed as a legitimate response to structural issues, while student mobilization is framed as a potential disruption that needs to be prevented. The structure of the coverage highlights differing emphases on actors deemed responsible, ranging from the government and police apparatus to organizers of protest calls. The main finding of this study indicates that Kompas.com consistently assigns different levels of legitimacy to mobilization based on group identity and underscores the media’s role in shaping public perceptions of social movements.